MEDIA KAMPANYE PADA “KONTAN MONEYFEST GREENERACTION 2023” DENGAN MENERAPKAN ESG - Adimas Mahcaya, Lutfhinsyah; Hapsari, Wuri (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
The design of this campaign is in the form of a series of educational visuals for the MoneyFest event organized by Kontan, with the aim of increasing generation Z's financial literacy, especially regarding to ESG (Environmental, Social and Governance). This campaign combines talk shows with practitioners and influencers, mini expos, and entertainment elements to make it easier for the younger generation to understand business, investment and sustainability topics. The aim of this design is to produce a fun, colorful and attractive visual campaign for generation Z, so that they can more easily accept and understand the concepts of ESG and sustainability. The resulting design is aligned with the event theme